Monotonic and reverse-cyclic load experiment for plywood and RC slab diaphragms used in timber-concrete hybrid building. (August 2016) - Kawai, Naohito; Isoda, Hiroshi; Okabe, Minoru; Tesfamariam, Solomon
Abstract: In seismically active regions, the use of timber-reinforced concrete (RC) hybrid construction can overcome the structural limitations that occur with timber construction. A series of shake table tests were carried out on RC-timber hybrid systems that used two diaphragms: glulam + plywood system (CN75 @ 50 mm nail spacing) and laminated wood + RC slab system. To develop robust analytical models, however, understanding the different components is crucial. In this paper, a series of in-plane monotonic and reverse-cyclic tests were undertaken on two diaphragm systems and their connections. Salient features of each diaphragm (i.e. stiffness, ductility, and energy dissipation) were computed from the monotonic loading test results. With the test results reported, analytical and numerical models can be developed.